The Effect Of Leadership Style And Career Development On Employee Performance At Cv Setia Kawan Medan - Suherman, Suherman; Syaifuddin, Syaifuddin; Faris, Salman (International Journal of Science, Technology & Management, 2022)
The purpose of the study was to determine the effect of leadership style and career development on employee performance at CV Setia Kawan Medan. The data analysis method used in this study is a statistical analysis method using multiple linear regression equations. The research population is 45 employees who work in CV Setia Kawan. So the number of samples is the same as the population of 45 employees. Researchers tested the classical assumptions first before doing regression testing. The results showed that the calculated F value (8.907) was greater than the F table value (3.214), and sig.? (0.000a) was smaller than 5% alpha (0.05), so that leadership style and career development had a simultaneous effect. on employee performance at CV Setia Kawan Medan. Leadership style has an effect on employee performance at CV Setia Kawan Medan. Career development affects employee performance at CV Setia Kawan Medan. The influence of leadership style and career development on employee performance at CV Setia Kawan Medan is 80.2% while 19.8% is explained by other variables not included in this research model such as training, job stress and motivation.